The Effect of Long-Term Second-Generation Antipsychotics Use on the Metabolic Syndrome Parameters in Jordanian Population - Osama Abo Alrob; Sayer Alazzam; Karem Alzoubi; Mohammad B. Nusair; Haneen Amawi; Reema Karasneh; Abeer Rababa’h; Mohammad Nammas (Medicina, 2019)
Objectives: The aim of this study was to determine the incidence of metabolic syndrome in patients treated with second-generation antipsychotics (SGAs). Methods: In this retrospective study, we reviewed patients’ electronic medical records (EMRs) of all patients who received one SGA for at least six months, excluding patients who were taking other medications that are associated with significant effect on metabolic syndrome. Relevant clinical information was collected prior to starting the SGA and after six months of continuous use of the same SGA. Results: A total of 91 patients were included in the study. The majority of patients (72%) were diagnosed with schizophrenia. After six months of taking the SGA, 44% of patients experienced elevated systolic pressure, 54.9% had elevated triglyceride, and 31.9% had impaired glucose levels (p value < 0.05). Prior to initiating SGA therapy, 14.3% of patients had metabolic syndrome, while 37.4% had metabolic syndrome after six months of therapy, and it was more prominent in males compared to female patients (p value < 0.05). Conclusion: This study found a strong correlation between SGA use and the appearance of metabolic alterations, such as weight gain, glucose intolerance, and increased triglyceride levels. These findings highlight the importance of assessing metabolic deregulations to minimize SGA associated metabolic abnormalities.